Taxonomic revision of the Tabanus nebulosus species group (Diptera: Tabanidae) - Dutra, Maria Carolina Pimenta; Amorim, Dalton De Souza; Carmo, Daniel Dias Dornelas Do (Zootaxa, 2025)
The genus Tabanus Linnaeus, 1758 is the most species-rich in the family Tabanidae (Diptera: Brachycera), with about 1,350 valid species. Evidence suggests that the genus is not monophyletic, i.e., there are some smaller clades also with generic rank that phylogenetically fit inside Tabanus. To deal with the complexity of the genus, previous research divided the Neotropical Tabanus fauna into nine groups of species based on morphological similarity. The T. nebulosus group has a considerably uniform morphology among its twelve species and there is evidence that it corresponds to a small clade within the genus. There are records of economic importance of the species of the group. Some species are potential vectors of bovine trypanosomiasis, which causes severe anemia and weight loss in cattle. There are pending issues in the taxonomy of this group, both in terms of a better understanding of the species composition and of species delimitation. This paper corresponds to a taxonomical review of the species related to T. nebulosus. Here we provide a diagnosis of the known species of the group, a pictorial key with high-definition images, and updated distribution maps for the valid species. Also, considering the limits of each species based on a careful morphological assessment of the group, the status of Tabanus ornativenris Kröber is evaluated and Tabanus vestigium sp. nov. is described from the state of São Paulo, Brazil.